2015
DOI: 10.1088/1748-0221/10/01/c01037
|View full text |Cite
|
Sign up to set email alerts
|

Proton irradiation of a swept charge device at cryogenic temperature and the subsequent annealing

Abstract: A number of studies have demonstrated that a room temperature proton irradiation may not be sufficient to provide an accurate estimation of the impact of the space radiation environment on detector performance. This is a result of the relationship between defect mobility and temperature, causing the performance to vary subject to the temperature history of the device from the point at which it was irradiated. Results measured using Charge Coupled Devices (CCD) irradiated at room temperature therefore tend to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…staying cold). The temperature aspect requires a study to confirm if the same performance is achieved if the device is irradiated at one temperature to if it is irradiated colder 17 and then allowed to warm to that temperature, this is planned for the near future and will include the side by side irradiation of an n-channel and p-channel CCD204. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…staying cold). The temperature aspect requires a study to confirm if the same performance is achieved if the device is irradiated at one temperature to if it is irradiated colder 17 and then allowed to warm to that temperature, this is planned for the near future and will include the side by side irradiation of an n-channel and p-channel CCD204. …”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned studies have shown that performing an irradiation at only room temperature can give misleading impressions of both the evolution of dark current, bright defects 6. 9-11, 15-17 and CTE 6,9,[12][13][14][15][16][17] . These factors can have a significant impact on the selection of the optimal operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, we are moving towards the use of cryogenic irradiations, that is, to irradiate the device whilst running and cold, keeping the device cold from the point of irradiation until the testing is completed. This is of course a more complex procedure than the standard room temperature irradiation, but the results observed, such as in Gow et al (2015) [42] and Murray et al (2014) [13], suggest that this is an important change to be made to the test procedure to get a more realistic indication of the performance degradation that might be expected in-orbit.…”
Section: Discussionmentioning
confidence: 99%
“…Additional investigations performed since this study have also presented findings that are consistent with this conclusion. A study performed by Gow et al (2015) 18 included the irradiation of a Swept Charge Device (SCD) at 238 K, where performance was seen to vary depending upon the subsequent room temperature anneal period. Also of note are the investigations performed by Hopkinson that entailed irradiation of CCD sensors that were flown on ESAs GAIA satellite 19 and also the investigations performed by Bautz et al (2005) for the Chandra X-ray observatory.…”
Section: Cryogenic Irradiationsmentioning
confidence: 99%